Answer:
a is the correct answer y =
Explanation:
To write the equation 4x - 3y = 12 in the form y=mx + b, we need to make y subject of the formula in the equation 4x - 3y = 12;
4x - 3y = 12
subtract 4x from both-side of the equation;
4x -4x -3y = 12 - 4x
-3y = 12- 4x
we want to make the left hand side of the equation positive, so we multiply through by a negative sign.
The equation becomes;
3y = -12 + 4x
We can rearrange this equation, hence;
3y = 4x - 12
Divide through by 3
(On the left hand side of the equation, the 3 numerator will cancel the 3 denominator leaving us with just y, on the right hand side of the equation 3 will divide -12 which will give us -4)
y =
- 4